Synthesis and Microwave Absorption Properties of Core-Shell Structured Co3O4-PANI Nanocomposites. (11th October 2015) - Xu, Hongyan; Hai, Zhenyin; Diwu, Jiangtao; Zhang, Qiang; Gao, Libo; Cui, Danfeng; Zang, Junbin; Liu, Jun; Xue, Chenyang
Abstract : The core-shell structured Co3 O4 -PANI nanocomposites have been successfully prepared using an in situ polymerization method, while the core Co3 O4 nanoparticles were synthesized by carbon-assisted method using degreasing cotton as a template. The obtained samples were characterized by XRD, TEM, FTIR, and XPS. The results indicated that the amorphous PANI was well covered on the surface of the spinel Co3 O4 and the Co3 O4 -PANI with core-shell structure was formed with particle size of about 100 nm. The interfacial interaction of the core-shell nanocomposite greatly enhances the microwave absorption properties. The maximum reflection loss of Co3 O4 -PANI is up to −45.8 dB at 11.7 GHz with a thickness of 2.5 mm and the adsorption bandwidth with the reflection loss below −10 dB reaches 14.1 GHz ranging from 3.9 to 18 GHz when the thickness is between 2 and 5.5 mm. Therefore, the facilely synthesized and low-cost Co3 O4 -PANI nanocomposite with superior microwave absorption properties can be a promising nanomaterial for high efficient microwave absorption.